PERWUJUDAN HISTORIS SEBAGAI REPERTOIRE DALAM TENGGELAMNYA KAPAL VAN DER WIJCK KAJIAN ESTETIKA WOLFGANG ISER - Daratullaila Nasri (tuahtalino, 2020)
This paper reviews historical materialization as repertoire in Hamka's Tenggelamnya Kapal van der Wijck novel. Repertoire is a concept attached to a theory of aesthetic response by Wolfgang Iser. Repetoire is a collection of knowledge owned by authors, consisting cultural elements (history, social, culture). Research method focused on aesthetic response which is about reading strategy and the interaction between text and its reader. It resulted in historical materialization in the form of background and foreground. "Paham Merah"/"Red Idealism" or PKI that appears in the text is stated as background in Tenggelamnya Kapal van der Wijck novel. Background leads reder's interpretation to understand foreground which is Zainuddin was PKI historical figure in Padang Panjang, Natar Zinuddin. It is supported by the presence of Muluk—Zainuddin's best friend—whom related to Muluk Nasution. The effect of idealism brought by them was the ups and downs of Haji Rasul's career in Sumatera Thawalib. It is also interpreted in a drama titled "Terusir" and "Kembali" by Zainuddin.